2010
DOI: 10.1271/bbb.90617
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an N-Terminal Acidic Amino Acid-Specific Aminopeptidase from Soybean Cotyledons (Glycine max)

Abstract: A novel enzyme that catalyzes the efficient hydrolysis of Glu-Glu was isolated from soybean cotyledons by ammonium sulfate fractionation and successive column chromatographies of Q-sepharose, Phenyl sepharose, and Superdex 200. The apparent molecular mass of this enzyme was found to be 56 kDa and 510 kDa by SDSpolyacrylamide gel electrophoresis and Superdex 200 HR 10/30 column chromatography respectively. The enzyme had high activity against Glu-p-nitroanilide (pNA) and Asp-pNA, whereas Leu-pNA, Phe-pNA, AlapN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The estimated molecular weights of AP1 and AP2 were ∼97 and 42.8 kDa respectively. These molecular weights of pigeonpea seed APs were similar to that of several plant APs reported (Yamaoka et al, 1994;Arima et al, 2000;Ogiwara et al, 2005;Strelec et al, 2009;Tishinov et al, 2009;Asano et al, 2010). While evaluating substrate specificity of inducible pigeonpea seed AP, it was found that the enzyme was preferentially cleaved LpNA.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The estimated molecular weights of AP1 and AP2 were ∼97 and 42.8 kDa respectively. These molecular weights of pigeonpea seed APs were similar to that of several plant APs reported (Yamaoka et al, 1994;Arima et al, 2000;Ogiwara et al, 2005;Strelec et al, 2009;Tishinov et al, 2009;Asano et al, 2010). While evaluating substrate specificity of inducible pigeonpea seed AP, it was found that the enzyme was preferentially cleaved LpNA.…”
Section: Discussionsupporting
confidence: 82%
“…The broad pH optimum is due to the titration of three functional groups in the active enzyme centre. Similar broad pH activity profiles were reported for various purified plant APs (Arima et al, 2000;Ogiwara et al, 2005;Strelec et al, 2009;Asano et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The changes in the levels of free amino acids during soybean germination were measured by HPLC analysis, indicating that the total contents of free amino acids were increased from 515.78 up to 847.44 mg mL −1 (S3 yogurt) and 880.75 mg mL −1 (S6 yogurt) due to the germination (Yang & Li, ). The increase in free amino acids content was attributed to the hydrolysis of polypeptide chains of storage proteins by endogenic exopeptidases during the germination of soybean seeds (Kubota et al ., ; Asano et al ., ). Soy protein, one of the main components of soybean, plays an important role in the performance of soy products, for example soy yogurt.…”
Section: Resultsmentioning
confidence: 97%
“…The Arabidopsis thaliana asparaginase 1 (At5g08100) has isoaspartyl dipeptidase activity [20, 21]. In addition, a multimeric aminopeptidase that hydrolyzes Glu and Asp residues from peptides and β-naphthylamide substrates was identified in soybean cotyledons [22]. The soybean aminopeptidase is three fold more active on substrates with N-terminal Glu residues.…”
Section: Introductionmentioning
confidence: 99%